2014
DOI: 10.1128/microbiolspec.mgm2-0021-2013
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Capsular Polysaccharides and Cell Envelope (Glyco)lipids

Abstract: This chapter summarizes what is currently known of the structures, physiological roles, involvement in pathogenicity and biogenesis of a variety of non-covalently bound cell envelope lipids and glycoconjugates of Mycobacterium tuberculosis and other Mycobacterium species. Topics addressed in this chapter include phospholipids; phosphatidylinositol mannosides; triglycerides; isoprenoids and related compounds (polyprenyl phosphate, menaquinones, carotenoids, non-carotenoid cyclic isoprenoids); acyltrehaloses (li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 359 publications
(457 reference statements)
0
63
0
Order By: Relevance
“…The mycolic acids form a second lipid bilayer which constitutes a diffusion barrier similar to the outer membrane of Gram-negative bacteria (11) (for a recent review on the structure and assembly of the mycobacterial cell wall, see reference 12). As corynebacteria and mycobacteria have no teichoic acids within their cell walls and only mycobacteria harbor capsule-like structures (13), the function of LCP proteins in these species and their relation to cell wall biosynthesis remains unclear. A recent study revealed that the LCP protein CpsA of Mycobacterium marinum plays an important role in cell wall assembly and that it is essential for proliferation in macrophages and virulence in zebrafish (14).…”
Section: Importancementioning
confidence: 99%
“…The mycolic acids form a second lipid bilayer which constitutes a diffusion barrier similar to the outer membrane of Gram-negative bacteria (11) (for a recent review on the structure and assembly of the mycobacterial cell wall, see reference 12). As corynebacteria and mycobacteria have no teichoic acids within their cell walls and only mycobacteria harbor capsule-like structures (13), the function of LCP proteins in these species and their relation to cell wall biosynthesis remains unclear. A recent study revealed that the LCP protein CpsA of Mycobacterium marinum plays an important role in cell wall assembly and that it is essential for proliferation in macrophages and virulence in zebrafish (14).…”
Section: Importancementioning
confidence: 99%
“…Studies conducted for decades to follow by generations of outstanding biochemists in France, the United Kingdom, and the United States, in particular, have resulted in a thorough understanding of the chemical structures of these lipids. Their detailed descriptions have been compiled in several recent books and reviews and the reader is referred to these for further reading on this topic (Brennan 1988;Barry et al 1998;Kaur et al 2009;Daffé et al 2014). Developments in the genetic manipulation of mycobacteria in the 1990s and the release of the first complete genome sequence of Mtb in 1998 have provided a major impetus to the study of the biosynthesis of these compounds with the result that many of the enzymes and transporters involved in their biogenesis have now been identified.…”
mentioning
confidence: 99%
“…tuberculosis has an unusual cell envelope, characterized by an outer membrane (the mycomembrane) consisting largely of long-chain mycolic acids (MA) and a number of atypical lipids (7,8). Most of these lipids are important to the viability and/or virulence of the bacteria (9), which is why much effort continues to be devoted to identifying, analyzing, and targeting enzymes involved in their metabolism (9)(10)(11)(12)(13). Consequently, much is known about the pathways responsible for biosynthesis of the mycolic acids and other components of the mycomembrane (Fig.…”
mentioning
confidence: 99%